THE INFLUENCE OF TRUST AND SATISFACTION ON CUSTOMER LOYALTY FOR GOJEK ONLINE TRANSPORTATION APPLICATIONS IN GORONTALO CITY - Harun, Meylan; Taan, Hapsawati; Isa, Ramlan Amir (Manager : Jurnal Ilmu Manajemen, 2023)
This study aims to find out how much trust affects customer loyalty to the Gojek online transportation app in Gorontalo City, how much satisfaction affects customer loyalty to the Gojek online transportation app in Gorontalo City and how much trust and satisfaction affect customer loyalty to the Gojek online transportation app in Gorontalo City.This study's population has not been identified.100 respondents can be sampled using the non-probability sampling method.A multiple linear regression analysis test is used in this study. According to the findings of the study, trust has a positive and significant impact on Gojek online transportation application customers' loyalty in Gorontalo City, satisfaction has a positive and significant impact on Gojek online transportation application customers in Gorontalo City, and both trust and satisfaction have a significant impact on Gojek online transportation application customers' loyalty in Gorontalo City simultaneously.